1974
DOI: 10.1042/cs0460569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nucleotides, Hormones, Ions and 1,25-Dihydroxycholecalciferol on 1,25-Dihydroxycholecalciferol Production in Isolated Chick Renal Tubules

Abstract: S U M M A R Y1, The production of 1,25-dihydroxycholecalciferol (1,25-DHCC) from tritiated 25-hydroxycholecalciferol was assessed in renal tubules prepared from vitamin D-deficient chicks.2. Cyclic AMP and dibutyryl cyclic AMP enhanced the production of 1,25-DHCC. 3. Bovine parathyroid hormone (BPTH) and its synthetic analogue either had no effect or inhibited the production of 1,25-DHCC when calcium was present in the extracellular medium, but enhanced the conversion when calcium was absent. BPTH increased a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0

Year Published

1976
1976
1987
1987

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 25 publications
5
26
0
Order By: Relevance
“…In our study, 2.5 mg/kg of DBcAMP remarkably increased plasma 1,25(OH)2D in a patient with PHP of Type I (Case 9) with a reciprocal decrease in plasma 24,25-(OH)2D. Relating to these findings, some workers demonstrated that CAMP or DBcAMP reproduced the stimulating effect of PTH on 1,25(OH)D2 production by in vitro or in vivo animal experiments (Rasmussen et al 1972;Larkins et al 1974;Horiuchi et al 1977). Taken together, it is suggested that DBcAMP stimulates 1a-hydroxylase activity and inhibits 24-hydroxylase activity in Type I PHP, and that the mechanism of production or inhibition of vitamin D metabolites after CAMP producing system is not impaired.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In our study, 2.5 mg/kg of DBcAMP remarkably increased plasma 1,25(OH)2D in a patient with PHP of Type I (Case 9) with a reciprocal decrease in plasma 24,25-(OH)2D. Relating to these findings, some workers demonstrated that CAMP or DBcAMP reproduced the stimulating effect of PTH on 1,25(OH)D2 production by in vitro or in vivo animal experiments (Rasmussen et al 1972;Larkins et al 1974;Horiuchi et al 1977). Taken together, it is suggested that DBcAMP stimulates 1a-hydroxylase activity and inhibits 24-hydroxylase activity in Type I PHP, and that the mechanism of production or inhibition of vitamin D metabolites after CAMP producing system is not impaired.…”
Section: Discussionsupporting
confidence: 51%
“…In addition, Rasmussen et al (1972), Larkins et al (1974) and Horiuchi et al (1977) reported that 3',5'-cyclic AMP(cAMP) or dibutyryl 3',5'-cyclic AMP(DBcAMP) reproduced the stimulating effect of PTH on 1,25-dihydroxyvitamin D3 production, suggesting that PTH action is mediated by cAMP.…”
mentioning
confidence: 99%
“…In contrast, in vitro evaluation ofcalcitonin effects on enzyme function have been controversial. Although Larkins et al (27) populations from Hyp-mice did not change. These studies are complicated by the difficulties inherent to the study of enzyme activity in an in vitro system as noted above.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in vitamin-D-deficient mitochondria calcium appears to have no direct effect on the 24-hydroxylase enzyme (Suda et al, 1974). In isolated renal tubules Shain (1972) and Larkins et al, (1974) showed that added calcium had no effect on the production of 1,25-(OHhDa. Henry et al (1974) showed an inverse relationship between serum calcium levels and l-hydroxylase activity-a relationship which held in both intact and parathyroidectomised (PTX) chicks.…”
Section: A the Role Of Ionsmentioning
confidence: 99%
“…Fraser and Kodicek (1973) obtained similar results in experiments with parathyroidectomised chicks. Rasmussen et al (974) and Larkins et al (1974) stimulated 1,25-(OHhDa production in isolated renal tubules with both PTH and its intracellular messenger cyclic AMP. It should be noted that Larkins et al (1974) were able to produce stimulation by PTH only under conditions of extreme calcium depletion of the incubation medium, leading them to suggest that the tendency of PTH to drive calcium into cells might overcome the other effect of the hormone, that is of stimulating l-hydroxylase activity by a cyclic AMP-mediated process.…”
Section: B the Role 0/ Calciostatic Hormonesmentioning
confidence: 99%